A surface-based approach to determine key spatial parameters of the acetabulum in a standardized pelvic coordinate system. (February 2018) - Chen, Xiaojun; Jia, Pengfei; Wang, Yiping; Zhang, Henghui; Wang, Liao; Frangi, Alejandro F.; Taylor, Zeike A.
Highlights: A semi-automatic surface-based method to determine acetabular parameters is proposed. A standardized pelvic coordinate system with the APP, MSP, and TPP is established. The experiment demonstrated the efficiency and reproducibility of our method. Abstract: Accurately determining the spatial relationship between the pelvis and acetabulum is challenging due to their inherently complex three-dimensional (3D) anatomy. A standardized 3D pelvic coordinate system (PCS) and the precise assessment of acetabular orientation would enable the relationship to be determined. We present a surface-based method to establish a reliable PCS and develop software for semi-automatic measurement of acetabular spatial parameters. Vertices on the acetabular rim were manually extracted as an eigenpoint set after 3D models were imported into the software. A reliable PCS consisting of the anterior pelvic plane, midsagittal pelvic plane, and transverse pelvic plane was then computed by iteration on mesh data. A spatial circle was fitted as a succinct description of the acetabular rim. Finally, a series of mutual spatial parameters between the pelvis and acetabulum were determined semi-automatically, including the center of rotation, radius, and acetabular orientation. Pelvic models were reconstructed based on high-resolution computed tomography images. Inter- and intra-rater correlations for measurements of mutual spatial parameters were almost perfect, showing our method affords very reproducible measurements. The approach will thus be useful for analyzing anatomic data and has potential applications for preoperative planning in individuals receiving total hip arthroplasty.